Exploration e exploitation na estratégia de diversificação da indústria sucroalcooleira paulista - Santos, Fábia Maria Silva Lins dos (2007)
Traditionally, the sugar cane sector is commodities industry and rarely innovate its portfolio, although researches have shown that some firms inside the sector have been using portfolio diversification strategies in the search of growth. Inside these strategies, the firms have made choices to: prospect new knowledge (exploration) or take advantage of not utilized competencies (exploitation). The use of knowledge is part of sectoral systems of innovation due to actors and institutions interaction. Using an exploratory and multicase and multistrategy study, this project wants to verify which processes exploration or exploitation is predominant on diversification strategy of sugar cane firms. The main contribution of this study are related to three main objectives: (1) identify characteristics of diversification in the sugar cane plants; (2) distinguish the processes of exploration and exploitation in these plants; (3) present evidences that support the presupposition of sugar cane sector being a sectoral systems of innovation. The results have shown that, from a total of nine firms, eight of them developed diversification strategies, related to Penrose (1959) classification of diversification. All of them participated in the sectoral systems of innovation, interacting in major or minor degree. All researched firms presented process related to exploitation, but their punctuation in exploration may explain their search for diversification. The high punctuation at exploration of some firms suggests it may be an explanation of their differentiated portfolio. Furthermore they showed intensive interaction with universities and research entities, in the search for new knowledge. These findings where consistent with the main objective defined in this project. It is expected that the present study might support future researches upon knowledge generation in firms oriented to diversification strategies.